Judah and the Judeans in the Fourth Century B.C.E - Achenbach, Reinhard; Albertz, Rainer 1943-; Albertz, Rainer 1943-; Becking, Bob; Ben Zvi, Ehud 1951-; Blenkinsopp, Joseph; Eshel, Esther; Eshel, Hanan; Grabbe, Lester L; Kloner, Amos; Knoppers, Gary 1956-2018; Knoppers, Gary 1956-2018; et al. (University Park, PA Penn State University Press, 2021)
Frontmatter -- Contents -- Abbreviations -- Introduction -- Part 1. The History of the Fourth Century: A View from the Center -- The Achaemenid Empire in the Fourth Century b.c.e.: A Period of Decline? -- Part 2 Judah in the Late Persian and Early Hellenistic Periods -- The Settlement Archaeology of the Province of Judah: A Case Study -- Administration in Fourth-Century b.c.e. Judah in Light of Epigraphy and Numismatics -- Yehud Stamp Impressions in the Fourth Century b.c.e.: A Time of Administrative Consolidation? -- “And They Did Not Care to Speak Yehudit”: On Linguistic Change in Judah during the Late Persian Era -- Archaeology and Archaiologias: Relating Excavations to History in Fourth-Century b.c.e. Palestine -- Part 3 Edom and Samaria: Judah’s Neighbors in the Late Persian and Early Hellenistic Periods -- Idumea in the Late Persian Period (Fourth Century b.c.e.) -- The Onomasticon of Mareshah in the Persian and Hellenistic Periods -- The Dating of the First Phase of the Samaritan Temple on Mount Gerizim in Light of the Archaeological Evidence -- Do the Earliest Samaritan Inscriptions Already Indicate a Parting of the Ways? -- The Governors of Samaria in the Fifth and Fourth Centuries b.c.e. -- Part 4 Biblical Literature in the Late Persian and Hellenistic Periods -- The Late Persian Formation of the Torah: Observations on Deuteronomy 34 -- The Pentateuch, the Prophets, and the Torah in the Fifth and Fourth Centuries b.c.e. -- The Canonical Alignment of the Book of Joshua -- Nehemiah and Sanballat: The Enemy Without or Within? -- A New Model for the Composition of Ezra-Nehemiah -- Who Knew What? The Construction of the Monarchic Past in Chronicles and Implications for the Intellectual Setting of Chronicles -- “Those Doing the Work for the Service in the House of the Lord” 1 Chronicles 23:6–24:31 and the Sociohistorical Context of the Temple of Yahweh in Jerusalem in the Late Persian/Early Hellenistic Period -- The Development of Jewish Sectarianism from Nehemiah to the Hasidim -- Index of Authors -- Index of Scripture -- Index of Sites
During the past decade, the period from the 7th century B.C.E. and later has been a major focus because it is thought to be the era when much of the Hebrew Bible/Old Testament was formed. As a result, there has also been much interest in the historical developments of that time and specifically in the status of Judah and its neighbors. Three conferences dealing roughly with a century each were organized, and the first conference was held in Tel Aviv in 2001; the proceedings of that conference were published as Judah and the Judeans in the Neo-Babylonian Period. The second volume was published in early 2006, a report on the conference held in Heidelberg in July 2003: Judah and the Judeans in the Persian Period.Judah and the Judeans in the Fourth Century B.C.E. is the publication of the proceedings of the third conference, which was held in Muenster, Germany, in August 2005; the essays in it focus on the century during which the Persian Empire fell to Alexander the Great and the Hellenistic kingdoms came to the fore.Participants whose contributions are published here are: R. Achenbach, R. Albertz, B. Becking, E. Ben Zvi, J. Blenkinsopp, E. Eshel, H. Eshel, L. L. Grabbe, A. Kloner, G. N. Knoppers, I. Kottsieper, A. Lemaire, O. Lipschits, Y. Magen, K. Schmid, I. Stern., O. Tal, D. Vanderhooft, J. Wiesehöfer, J. L. Wright, and J. W. Wright
[Online-Ausgabe]
Mode of access: Internet via World Wide Web.
In English
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Jews -- Congresses -- History -- 586 B.C.-70 A.D; Jews -- History -- 586 B.C.-70 A.D -- Congresses; Judaism -- Congresses -- History -- Post-exilic period, 586 B.C.-210 A.D; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D -- Congresses; HISTORY / Ancient / General